An investigation of weak CH...O hydrogen bonds in maltose anomers by a combination of calculation and experimental solid-state NMR spectroscopy. - Yates, JR; Pham, T; Pickard, C; Mauri, F; Amado, A; Gil, A; Brown, S (2005)
Two-dimensional (1)H-(13)C MAS-J-HMQC solid-state NMR spectra of the two anomeric forms of maltose at natural abundance are presented. The experimental (1)H chemical shifts of the CH and CH(2) protons are assigned using first-principles chemical shift calculations that employ a plane-wave pseudopotential approach. Further calculations show that the calculated change in the (1)H chemical shift when comparing the full crystal and an isolated molecule is a quantitative measure of intermolecular C-H...O weak hydrogen bonding. Notably, a clear correlation between a large chemical shift change (up to 2 ppm) and both a short H...O distance (<2.7 A) and a CHO bond angle greater than 130 degrees is observed, thus showing that directionality is important in C-H...O hydrogen bonding.